A production method of a 750mpa-grade high-strength zinc-aluminum-magnesium steel strip
Patent Information
- Application Number
- CN202611124484.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-10-16
AI Technical Summary
然而,现有高速公路护栏广泛采用热镀锌工艺,存在高耗能、高污染问题,镀层附着量增加后均匀性变差,不符合绿色环保发展要求;所用Q235钢强度不足,厚规格运输及施工效率低下且成本较高,无法有效防护重型车辆碰撞,富锌漆喷覆后耐蚀性差、使用寿命短,大幅增加检修养护成本,难以满足现行标准及低碳环保要求
1、本发明生产的锌铝镁钢带屈服强度≥700MPa,抗拉强度≥750MPa,断后伸长率A≥18%。本产品最终性能可完全适应各种环境下可移动式高速公路护栏对材料强度、塑韧性、耐腐蚀性、可加工性的严苛需求,生产工艺绿色环保,生产成本能耗低,可实现薄壁高强钢替代传统厚规格Q235材质的可移动式高速公路护栏,使护栏的防护能力达到优于现行T/CECS G:D83细则推荐的护栏形式,降低护栏材料使用量的同时,还可降低护栏的建设成本,具有显著的经济效益和广阔的产业化应用前景。
Smart Images

Figure CN122918451A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of high-strength steel zinc-aluminum-magnesium steel strip production methods, and particularly to a production method for 750MPa grade high-strength steel zinc-aluminum-magnesium steel strip. Background Technology
[0002] The current T / CECS G:D83 standard requires that the guardrail substrate use P17 samples with mechanical properties of yield strength ≥700MPa, tensile strength ≥750MPa, and elongation at break (A) ≥18%. However, existing highway guardrails widely use hot-dip galvanizing, which has high energy consumption and pollution problems. The uniformity of the coating deteriorates with increased coating thickness, failing to meet the requirements of green and environmentally friendly development. The Q235 steel used is not strong enough, and the transportation and construction of thick-gauge steel is inefficient and costly. It cannot effectively protect against heavy vehicle collisions. The zinc-rich paint has poor corrosion resistance and short service life, significantly increasing maintenance costs and failing to meet current standards and low-carbon environmental protection requirements.
[0003] Against this backdrop, there is an urgent need to develop a high-strength, high-toughness, and high-corrosion-resistant material that can be applied to highway guardrails. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a method for producing 750MPa grade high-strength zinc-aluminum-magnesium steel strip.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows: A method for producing 750MPa grade high-strength zinc-aluminum-magnesium steel strip includes the following steps: Blast furnace smelting of molten iron → KR desulfurization pretreatment of molten iron → 120-ton top and bottom combined blowing CO2 converter smelting → LF refining → CSP thin slab continuous casting → transverse tunnel heating furnace → TMCP six-stand four-roll continuous rolling → segmented laminar flow cooling → U-shaped coiling → inspection and warehousing. The chemical composition of the steel strip, by weight percentage, is as follows: C: 0.060–0.070 wt%, Si: 0.10–0.30 wt%, Mn: 1.25–1.40 wt%, P: ≤0.015 wt%, S: ≤0.010 wt%, Als: 0.020–0.045 wt%, V: 0.040–0.050 wt%, Ti: 0.130–0.150 wt%, Cr: 0.25–0.40 wt%, Ca: 0.0020–0.0050 wt%, with the remainder being Fe and unavoidable trace elements.
[0006] In the converter smelting process, the S content of the molten iron is ≤0.035wt%; carbon dioxide is blown from the bottom throughout the smelting process, at a concentration of 0.02m³. 3 / (t·min)<bottom-blown gas supply intensity≤0.05m3 / (t·min); The final dissolved [O] in molten steel is controlled at 600-850ppm, and steel sand is used for deoxidation and alloying with aluminum deoxidation, and SiMnFe, SiFe, and LCMnFe are used to prepare Si and Mn.
[0007] In the LF refining process, the molten steel undergoes aluminum deoxidation, V, Ti, and Cr microalloying, and calcium treatment in the LF furnace. The microalloying and calcium treatment processes are carried out with a wire feeding speed of 3-3.5 m / s and a soft blowing time of 6 min after calcium treatment.
[0008] In the CSP thin slab continuous casting process, a two-strand vertical bending CSP thin slab continuous casting process is adopted. The casting process requires ladle protection casting and ladle slag detection and control. The tundish temperature is 1545~1565℃, the billet casting speed is ≥3.6m / min, carbon-free covering agent is used in the tundish, and low-carbon steel protective slag is used in the crystallizer to remove slag and protect carbon. The liquid level fluctuation in the crystallizer is controlled within ±3mm to ensure continuous casting.
[0009] In the transverse roller bottom tunnel heating furnace, the furnace outlet temperature is controlled at 1170-1200℃, and the billet heating temperature is 1155-1170℃. This ensures the billet is held in the furnace for a certain period of time, allowing the microalloying elements to be completely dissolved in the austenite region and controlling the expansion of the austenite region.
[0010] In the continuous rolling process, the TMCP six-stand four-high continuous rolling process is adopted, with large reduction deformation. The reduction of F1, F2 and F3 mills is controlled to promote ferrite nucleation and refine grains. The reduction rates of F1, F2 and F3 mills are controlled at 55%, 45% and 35% or higher, respectively. High-pressure water descaling is ensured during the rolling process, with an inlet pressure of 200-260 bar, an outlet pressure of 300-380 bar, a cooling rate of more than 20℃ / s, and a final rolling temperature of 900-940℃.
[0011] In the segmented laminar flow cooling, a multi-segment high-efficiency densified laminar flow cooling system consisting of a densified fine-tuning segment, a coarse-tuning segment, and another densified fine-tuning segment is adopted to achieve precise control of the internal structure of high-strength steel.
[0012] In the U-shaped winding process, the winding tension is 15-28KN, and the winding temperature is 570-630℃.
[0013] This invention also includes the following steps for continuous hot-dip galvanizing of high-strength steel with aluminum-magnesium coating: inlet uncoiling → laser welding → disc shearing → scale breaking machine → three-stage turbulent pickling → re-brushing and grinding → leveling machine → electromagnetic induction heating furnace → zinc pot → air knife → fan cooling → water quenching tank → finishing machine → tension leveling machine → roller coating machine → induction heating furnace → cooling air box → oiling → outlet coiling.
[0014] In the laser welding process, the welding speed is 38 mm / s, the welding machine power is 1500W, the laser diameter is 0.2 mm, and the defocusing amount is 295±0 mm. In the disc shearing edge: the shearing amount on one side is 10mm; In the three-stage turbulent pickling process: the acid bath temperature is 80℃ and the conductivity is 360ms / cm; In the re-brushing process: the re-brushing brush roller mode is 7 with an inlet brush roller mode of 1200 rpm and the outlet brush roller mode is 7 with a speed of 1200 rpm. In the leveling mill: the rolling force is 3500-4000KN, and the elongation is 0.3%; In the electromagnetic induction heating furnace: IH1 section 410℃, IH2 section 589℃, RTS section 670℃, HB section 419℃; hydrogen content 8%, process speed 50m / min; In the zinc pot: the zinc pot temperature is 440-450℃, the zinc liquid contains 10-22 wt% Al, 2-6 wt% Mg, 0.2±0.02 wt% Si, 0.01±0.002 wt% Ni, 0.05±0.02 wt% Ce, 0.05±0.02 wt% Ti, and the remainder consists of unavoidable impurity elements and Zn, with the total impurity element content not exceeding 1%. In the air knife: the air knife is 22mm away from the strip, the air knife pressure is 31mbar, the air knife height from the liquid surface is 125mm, the air knife lip gap is 1.2-1.4mm in the middle 450mm, and increases to both sides in 90mm increments of 0.02mm, with the outermost gap being 1.35mm. The edge baffle is 6.0mm thick and the distance between the edge baffle and the strip is 2mm. The main purpose is to reduce the thickening of the coating at the edge of the strip. During the cooling process of the fan: the cooling air volume of the fixed air box 0 is 20%, the air volume of the mobile cooling air box 1 is 75%, the air volume of the air box 2 is 82%, the air volume of the air box 1 in the upward section is 84%, the air volume of the air box 2 is 20%, the air volume of the air box 3 is 18%, the air volume of the air box 4 is 26%, the air volume of the air box 5 is 85%, and the temperature at the top of the tower is ≤256℃; In the aforementioned finishing mill: the rolling force is 2110KN, and the elongation is 0.02%; The tension leveling machine has a tension of 70T and an elongation of 0.15%. In the roller coating machine: the roller coating machine pressure is 3550KN, the roller speed ratio is 1 / 1.6, and the roller coating liquid is a chromium-free fingerprint-resistant passivation liquid; In the induction heating furnace: the heating temperature is 118℃; During the exit winding process: the winding tension is 180KN, and the winding speed is 55m / min.
[0015] The role of chemical components in this invention and their impact on material properties: C: As a solid solution strengthening element, C can significantly improve the strength of the matrix through solid solution strengthening, making it the most significant contributor to the strength of steel. The higher the content, the higher the strength; however, excessive C will reduce the toughness and ductility of the steel. Conversely, lower C content increases ductility and toughness but cannot guarantee effective strength. Therefore, to ensure the strength and formability requirements of the zinc-aluminum-magnesium high-strength steel for movable highway guardrails, the C content in this invention is controlled at 0.060–0.070 wt%.
[0016] Mn: Similar to C, Mn can enhance the strength of the matrix through solid solution strengthening. Simultaneously, Mn can strengthen the ferrite phase transformation region and refine grains, improving the matrix's strength and toughness. Furthermore, appropriate amounts of Mn and S readily combine to form MnS, inhibiting FeS precipitation at grain boundaries, counteracting the harmful effects of S in the matrix, and improving processing and forming properties. In this invention patent, the Mn content is controlled at 1.25–1.40 wt%.
[0017] Si: Si has the same solid solution strengthening effect in steel, which is beneficial to improving the yield and tensile strength of steel; however, at high temperatures, excessive Si easily oxidizes iron scale to form Fe2SiO4 spinel phase, which is difficult to remove during subsequent descaling and easily forms microcracks due to oxide indentation on the surface. In order to obtain steel plates with high strength, good formability and surface quality, the Si content of this invention is controlled at 0.10-0.30 wt%.
[0018] V: V is a microalloying strengthening element and a strong carbon and nitrogen compound forming element. It mainly provides precipitation strengthening by precipitating dispersed and fine carbonitrides (V(C,N)), pinning dislocations; during the rolling and cooling process, it inhibits austenite grain growth and refines ferrite grains, achieving a significant grain refinement strengthening effect; thus, it can improve the strength of the matrix without compromising plasticity and toughness. The V content in this invention patent is controlled at 0.040 to 0.050 wt%.
[0019] Ti: Ti has a certain solubility in steel. At high temperatures, it readily forms stable (Ti(C,N)) compounds with carbon and nitrogen compounds. It can significantly improve the strength, toughness and corrosion resistance of steel, while improving the performance of the weld heat-affected zone. The movable highway guardrail of this invention uses a 750MPa grade high-strength steel zinc-aluminum-magnesium steel strip with V and Ti micro-alloying design, and the Ti content is 0.13 to 0.15 wt%.
[0020] P and S: S and P are generally considered harmful elements in steel, and their content must be strictly controlled. S causes hot brittleness in steel, reducing toughness and machinability; P causes cold brittleness in steel, reducing toughness and weldability. Furthermore, sulfide inclusions in steel also significantly affect the properties of steel in different directions. Based on the development trend of modern steel materials, it is necessary to minimize the sulfur content in steel and control sulfide inclusions. In this invention, S is controlled below 0.010 wt%, and P is controlled below 0.015 wt%.
[0021] Ca: mainly used for desulfurization and deoxidation, refining inclusions in steel, improving the toughness and weldability of steel, reducing hot brittleness, and enhancing the corrosion resistance of steel. In this invention, the Ca content is 0.0020 to 0.0050 wt%.
[0022] Als: A powerful deoxidizing element in steel, which can reduce oxide inclusions in steel, purify steel, improve the formability and impact performance of steel plates, and inhibit the aging hardening of steel to a certain extent. In this invention, the Als content is 0.020 to 0.045 wt%.
[0023] Cr: Improves the strength, hardness, and wear resistance of steel, effectively enhances its corrosion resistance (especially atmospheric corrosion resistance), refines austenite grains, and improves the high-temperature performance of steel. In this invention, the Cr content is 0.25–0.40 wt%.
[0024] Zn: As the core element of the coating, it precipitates as a Zn-rich phase during solidification. Its core function is sacrificial anode protection. It corrodes preferentially over the steel substrate, forming a dense corrosion product layer, which delays the corrosion of the steel substrate, extends the service life of the component, and is suitable for complex outdoor corrosive environments. In this invention, the Zn content is the coating balance.
[0025] Al: As the skeleton of the alloy coating, it preferentially precipitates and solidifies from the solution to form an Al-rich dendritic phase, which usually exists in a fishbone-like form. It can significantly improve the corrosion resistance of the coating, reduce the porosity of the coating, and block the penetration of corrosive media (water, oxygen, etc.). It avoids oxidation and powdering of the coating during high-temperature processing or long-term outdoor service, and is suitable for the production needs of thick coatings. The Al content in this invention is 10.8-22.0%.
[0026] Mg: Mg readily combines with Zn and Al to form a more stable Zn / MgZn2 / Al ternary alloy phase, further densifying the coating structure and enhancing corrosion resistance; at the same time, it improves the self-healing ability of the coating cuts. In this invention, the Mg content is 2.8-6.0%.
[0027] The beneficial effects of this invention are: 1. The zinc-aluminum-magnesium steel strip produced by this invention has a yield strength ≥700MPa, tensile strength ≥750MPa, and elongation after fracture (A) ≥18%. The final performance of this product fully meets the stringent requirements of movable highway guardrails in various environments for material strength, toughness, corrosion resistance, and processability. The production process is green and environmentally friendly, with low production costs and energy consumption. It enables the replacement of traditional thick-gauge Q235 material with thin-walled high-strength steel for movable highway guardrails, achieving a protective capability superior to the guardrail type recommended by the current T / CECS G:D83 detailed rules. This reduces the amount of guardrail material used and construction costs, resulting in significant economic benefits and broad prospects for industrial application.
[0028] 2. This invention adopts a design concept of low carbon, high manganese, (V, Ti) microalloying reinforcement. By precisely controlling the alloy composition, CSP production process and TMCP six-stand four-roll continuous rolling process, it obtains a steel strip with stable chemical composition and mechanical properties, high strength, good plasticity and toughness. At the same time, a zinc-aluminum-magnesium coating is applied to the surface to form a high-strength zinc-aluminum-magnesium steel strip with high corrosion resistance, which meets the requirements for steel used in movable highway guardrails.
[0029] 3. This invention uses V and Ti composite microalloying to control strength. Through the grain-refining strengthening effect and precipitation strengthening mechanism of V and Ti alloying elements, the strength is improved and the grains are refined. Furthermore, the microstructure is further refined through recrystallization controlled rolling technology, and the grain size reaches level 12.
[0030] 4. The addition of Cr not only further improves the strength and toughness of the substrate, but also enhances the corrosion resistance of the matrix itself, further strengthening the corrosion resistance of high-strength steel zinc-aluminum-magnesium steel strip, which is highly in line with the development requirements of green and environmentally friendly materials. Attached Figure Description
[0031] Figure 1 These are metallographic images of hot-rolled sheet coils from Embodiment 1 of the present invention; Figure 2 This is a metallographic image of a hot-dip galvanized aluminum-magnesium sheet coiled according to Embodiment 1 of the present invention; Figure 3 This describes the surface morphology of the hot-dip galvanized aluminum-magnesium sheet in Embodiment 1 of the present invention. Figure 4 These are real-world photos of the application of the high-strength steel zinc-aluminum-magnesium steel strip in the movable highway guardrail of Embodiment 1 of the present invention. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that these descriptions are merely exemplary and not intended to limit the scope of the invention. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concepts of the invention.
[0033] Example 1 The following embodiments employ the CSP thin slab continuous casting and rolling process to produce 750MPa high-strength zinc-aluminum-magnesium steel strip for highway guardrails using V and Ti composite microalloying technology. The process flow is as follows: blast furnace smelting of molten iron → KR desulfurization pretreatment of molten iron → 120-ton top and bottom blowing CO2 converter smelting → LF refining → CSP thin slab continuous casting → transverse tunnel heating furnace → TMCP six-stand four-roll continuous rolling → segmented laminar flow cooling → U-shaped coiling → inspection and warehousing; the method for preparing the continuous hot-dip galvanized aluminum-magnesium coating on the high-strength steel is as follows: inlet uncoiling → laser welding → disc shearing → scale breaking machine → three-stage turbulent pickling → re-brushing and grinding → leveling machine → electromagnetic induction heating furnace → zinc pot → air knife → fan cooling → water quenching tank → finishing machine → tension leveling machine → roll coating machine → induction heating furnace → cooling air box → oiling → outlet coiling; wherein: The chemical composition of the 750MPa highway guardrail steel strip is as follows: C: 0.065wt%, Si: 0.20wt%, Mn: 1.30wt%, P: ≤0.010wt%, S: ≤0.007wt%, Als: 0.025wt%, V: 0.045wt%, Ti: 0.14wt%, Cr: 0.30wt%, Ca: 0.0020~0.0035wt%, with the remainder being iron and unavoidable trace elements.
[0034] In the converter smelting process: a 120-ton BOF combined blowing converter is used, and the sulfur content of the molten iron fed into the converter is ≤0.035wt%; the smelting process adopts bottom blowing CO2 throughout, with a bottom blowing gas supply intensity greater than 0.02~0.05m. 3 / (t·min); the final dissolved [O] in molten steel is controlled at 600~850ppm; AlFe is used for deoxidation and alloying, and SiMnFe, SiFe, and LCMnFe are used to prepare Si and Mn; CO2 is blown throughout the tapping process, the liquid surface is blown open by 300~500mm, and argon is blown after the furnace for ≥8min.
[0035] In the LF furnace refining process: after the molten steel is smelted in the converter, it undergoes aluminum deoxidation, (V, Ti) microalloying, and calcium treatment in the LF furnace. The processing technology involves a wire feeding speed of 3.5–4.0 m / s and a weak blowing time of 8 min after calcium treatment to ensure the modification and spheroidization rate of non-metallic inclusions such as MnS and Al2O3 in the steel, so that the inclusions can float fully and improve the cleanliness of the molten steel.
[0036] In the CSP thin slab continuous casting process: a two-strand vertical curved CSP thin slab continuous casting process is adopted, followed by converter smelting and LF furnace refining. In the smelting production and casting process, the requirements are to protect the ladle during casting and to detect and control the slag runoff from the ladle. Low-carbon steel special protective slag is used. The temperature of the continuous casting tundish is controlled at 1555℃, the billet casting speed is 3.8 m / min, carbon-free covering agent is used in the tundish, low-carbon steel protective slag is used in the crystallizer, and the liquid level fluctuation in the crystallizer is controlled within ±3mm.
[0037] In the transverse roller bottom tunnel heating furnace: the furnace outlet temperature is controlled at 1180℃, the billet heating temperature is 1160℃, and the billet is kept at the furnace for a certain time to allow the microalloying elements to be fully dissolved and refined to improve the grain size.
[0038] In the hot continuous rolling process: the TMCP six-stand four-high hot continuous rolling process is adopted, focusing on controlling the reduction in the first three passes to ensure that the large reduction rolling forms a deformation zone and promotes grain nucleation; the finished product specification is 2.5×1150 mm, and the reduction rates of F1, F2 and F3 mills are controlled at 56.5%, 47.8% and 38.5% respectively; at least one high-pressure water descaling is guaranteed during the rolling process, with a descaling inlet pressure of 258 bar, an outlet pressure of 360 bar, a cooling rate of 21℃ / s, and a final rolling temperature of 920℃. The cooling mode of "front-stage ultra-fast cooling, middle-stage air cooling and rear-stage fine adjustment" is adopted, and the coiling temperature is 590℃.
[0039] In the laser welding process: welding speed 38mm / s, welding machine power 1500W, laser diameter 0.2mm, defocusing amount 295±0mm.
[0040] In the three-stage turbulent pickling process: the acid temperature in the acid tank is 80℃, and the conductivity is 360ms / cm.
[0041] In the re-brushing process: the re-brushing brush roller mode is 7 with an inlet brush roller mode of 1200 rpm and the outlet brush roller mode is 7 with a speed of 1200 rpm.
[0042] The leveling mill has a rolling force of 3750 kN and an elongation of 0.3%.
[0043] In the electromagnetic induction heating furnace: IH1 section 410℃, IH2 section 589℃, RTS section 670℃, HB section 419℃; hydrogen content 8%, process speed 50m / min.
[0044] The zinc pot contains: a temperature of 448°C, and the zinc liquid contains 11.12 wt% Al, 2.84 wt% Mg, 0.18 wt% Si, 0.007 wt% Ni, 0.04 wt% Ce, 0.03 wt% Ti, and the remainder consists of unavoidable impurity elements and Zn, with the total impurity element content not exceeding 1%.
[0045] In the air knife: the air knife is 22mm away from the strip, the air knife pressure is 31mbar, the air knife height from the liquid surface is 125mm, the air knife lip gap is 1.25mm in the middle of 450mm, and increases to both sides in 90mm increments of 0.02mm, with the outermost gap being 1.35mm. The edge baffle is 6.0mm thick and 2mm away from the strip. The main purpose is to reduce the thickening of the coating at the edge of the strip.
[0046] During the cooling process of the fan: the cooling air volume of the fixed air box 0 is 20%, the air volume of the mobile cooling air box 1 is 75%, the air volume of the air box 2 is 82%, the air volume of the upward section air box 1 is 84%, the air volume of the air box 2 is 20%, the air volume of the air box 3 is 18%, the air volume of the air box 4 is 26%, the air volume of the air box 5 is 85%, and the temperature at the top of the tower is ≤256℃.
[0047] In the aforementioned finishing mill: the rolling force is 2110KN and the elongation is 0.02%.
[0048] The tension leveling machine has a tension of 70T and an elongation of 0.15%.
[0049] The roller coating machine has a pressure of 3550KN, a roller speed ratio of 1 / 1.6, and the coating liquid is a chromium-free fingerprint-resistant passivation liquid.
[0050] In the induction heating furnace, the heating temperature is 118℃.
[0051] In the exit winding process: the winding tension is 180KN and the winding speed is 55m / min. After winding, zinc-aluminum-magnesium high-strength strip steel can be obtained.
[0052] The high-strength strip steel obtained in this embodiment has the following key indicators: hot-rolled mechanical properties: yield strength 658MPa, tensile strength 725MPa, elongation after fracture 23.8%; no edge defects; metallographic structure as shown in the figure. Figure 1 As shown: F+P+ carbides; grain size: grade 12; mechanical properties after zinc-aluminum-magnesium plating: yield strength 715MPa, tensile strength 780MPa, elongation after fracture 21.5%; no edge defects; metallographic structure as shown Figure 2 As shown: F+P+carbide; grain size: grade 12; fully compliant with the steel used for highway guardrail materials in traffic engineering.
[0053] The zinc-aluminum-magnesium high-strength strip steel coating produced in this embodiment has the following characteristics: Scanning electron microscope images of the coating surface and cross-section are shown below. Figure 3 As shown, the coating is mainly composed of Al-rich dendritic phase, Zn / MgZn2 binary alloy phase, and Zn / MgZn2 / Al ternary alloy phase. It has a dense microstructure, uniform and fine grains, and excellent corrosion resistance.
[0054] The zinc-aluminum-magnesium high-strength strip steel produced in this embodiment is used in the base of a movable highway guardrail, such as... Figure 4 As shown, zinc-aluminum-magnesium high-strength steel strips are hydraulically cut to length, punched, continuously rolled, and bolted together before being installed on the side of highways. Movable highway guardrails made from zinc-aluminum-magnesium high-strength steel strips feature good straightness, excellent corrosion resistance, no need for painting, and high strength with reduced thickness, achieving safe and stable operation, green and low-carbon construction, easy installation, and low maintenance costs.
[0055] .
[0056] Example 2 A method for producing 750MPa grade high-strength zinc-aluminum-magnesium steel strip includes the following steps: Blast furnace smelting of molten iron → KR desulfurization pretreatment of molten iron → 120-ton top and bottom combined blowing CO2 converter smelting → LF refining → CSP thin slab continuous casting → transverse tunnel heating furnace → TMCP six-stand four-roll continuous rolling → segmented laminar flow cooling → U-shaped coiling → inspection and warehousing. The steel strip has the following chemical composition by weight percentage: C: 0.060wt%, Si: 0.10wt%, Mn: 1.25wt%, P: 0.015wt%, S: 0.010wt%, Als: 0.020wt%, V: 0.040wt%, Ti: 0.130wt%, Cr: 0.25wt%, Ca: 0.0020wt%, with the remainder being Fe and unavoidable trace elements.
[0057] In the converter smelting process, the S content of the molten iron is ≤0.035wt%; carbon dioxide is blown into the bottom throughout the smelting process, with a bottom blowing gas supply intensity of 0.02m³ / min. 3 / (t·min); The final molten steel dissolved [O] was controlled at 600ppm, and steel sand aluminum was used for deoxidation and alloying, and SiMnFe, SiFe, and LCMnFe were used to prepare Si and Mn.
[0058] In the LF refining process, molten steel undergoes aluminum deoxidation, V, Ti, and Cr microalloying, and calcium treatment in the LF furnace. The microalloying and calcium treatment processes are carried out with a wire feeding speed of 3 m / s and a soft blowing time of 6 min after calcium treatment.
[0059] In the CSP thin slab continuous casting process, a two-strand vertical bending CSP thin slab continuous casting process is adopted. The casting process requires ladle protection casting and ladle slag detection and control. The continuous casting tundish temperature is 1545℃, the billet casting speed is 3.6m / min, carbon-free covering agent is used in the tundish, and low-carbon steel protective slag is used in the crystallizer to remove slag and protect carbon. The liquid level fluctuation in the crystallizer is controlled within ±3mm to ensure continuous casting.
[0060] In the transverse roller bottom tunnel heating furnace, the furnace exit temperature is controlled at 1170℃, the billet heating temperature is 1155℃, and the billet is kept at a constant temperature in the furnace to ensure that the microalloying elements are completely dissolved in the austenite region and to control the expansion of the austenite region.
[0061] In the continuous rolling process, the TMCP six-stand four-high continuous rolling process is adopted, with large reduction deformation. The reduction of F1, F2 and F3 mills is controlled to promote ferrite nucleation and refine grains. The reduction rates of F1, F2 and F3 mills are controlled at 55%, 45% and 35% or higher, respectively. High-pressure water descaling is ensured during the rolling process, with a descaling inlet pressure of 200 bar, an outlet pressure of 300 bar, a cooling rate of more than 20℃ / s, and a final rolling temperature of 900℃.
[0062] In the segmented laminar flow cooling, a multi-segment high-efficiency densified laminar flow cooling system consisting of a densified fine-tuning segment, a coarse-tuning segment, and another densified fine-tuning segment is adopted to achieve precise control of the internal structure of high-strength steel.
[0063] In the U-shaped winding process, the winding tension is 15KN and the winding temperature is 570℃.
[0064] This invention also includes the following steps for continuous hot-dip galvanizing of high-strength steel with aluminum-magnesium coating: inlet uncoiling → laser welding → disc shearing → scale breaking machine → three-stage turbulent pickling → re-brushing and grinding → leveling machine → electromagnetic induction heating furnace → zinc pot → air knife → fan cooling → water quenching tank → finishing machine → tension leveling machine → roller coating machine → induction heating furnace → cooling air box → oiling → outlet coiling.
[0065] In the laser welding process, the welding speed is 38 mm / s, the welding machine power is 1500W, the laser diameter is 0.2 mm, and the defocusing amount is 295±0 mm. In the disc shearing edge: the shearing amount on one side is 10mm; In the three-stage turbulent pickling process: the acid bath temperature is 80℃ and the conductivity is 360ms / cm; In the re-brushing process: the re-brushing brush roller mode is 7 with an inlet brush roller mode of 1200 rpm and the outlet brush roller mode is 7 with a speed of 1200 rpm. The leveling mill has a rolling force of 3500 kN and an elongation of 0.3%. In the electromagnetic induction heating furnace: IH1 section 410℃, IH2 section 589℃, RTS section 670℃, HB section 419℃; hydrogen content 8%, process speed 50m / min; In the zinc pot: the zinc pot temperature is 440℃, the zinc liquid contains 10wt% Al, 2wt% Mg, 0.202wt% Si, 0.012wt% Ni, 0.07wt% Ce, 0.07wt% Ti, and the remainder consists of unavoidable impurity elements and Zn, with the total impurity element content not exceeding 1%. In the air knife: the air knife is 22mm away from the strip, the air knife pressure is 31mbar, the air knife height from the liquid surface is 125mm, the air knife lip gap is 1.2mm in the middle 450mm, and increases to both sides in 90mm increments of 0.02mm, with the outermost gap being 1.35mm. The edge baffle is 6.0mm thick and the distance between the edge baffle and the strip is 2mm. The main purpose is to reduce the thickening of the coating at the edge of the strip. During the cooling process of the fan: the cooling air volume of the fixed air box 0 is 20%, the air volume of the mobile cooling air box 1 is 75%, the air volume of the air box 2 is 82%, the air volume of the air box 1 in the upward section is 84%, the air volume of the air box 2 is 20%, the air volume of the air box 3 is 18%, the air volume of the air box 4 is 26%, the air volume of the air box 5 is 85%, and the temperature at the top of the tower is ≤256℃; In the aforementioned finishing mill: the rolling force is 2110KN, and the elongation is 0.02%; The tension leveling machine has a tension of 70T and an elongation of 0.15%. In the roller coating machine: the roller coating machine pressure is 3550KN, the roller speed ratio is 1 / 1.6, and the roller coating liquid is a chromium-free fingerprint-resistant passivation liquid; In the induction heating furnace: the heating temperature is 118℃; During the exit winding process: the winding tension is 180KN, and the winding speed is 55m / min.
[0066] The hot-rolled high-strength strip steel produced in this embodiment has the following properties: Mechanical properties: yield strength 620 MPa, tensile strength 690 MPa, elongation after fracture 22%; Metallographic structure: F+P+carbides; Grain size: grade 11. The high-strength zinc-aluminum-magnesium steel strip has the following properties: yield strength 700 MPa, tensile strength 750 MPa, elongation after fracture 20%; Metallographic structure: F+P+carbides; Grain size: grade 11; 180° bending test: no cracking of the substrate, no peeling of the coating; Passivation solution film thickness on both the upper and lower surfaces controlled at 0.9 g / m. 2 The adhesion amount of the zinc-aluminum-magnesium alloy coating on a single side and at a single point is controlled at 60g / m². 2 .
[0067] Example 3 A method for producing 750MPa grade high-strength zinc-aluminum-magnesium steel strip includes the following steps: Blast furnace smelting of molten iron → KR desulfurization pretreatment of molten iron → 120-ton top and bottom combined blowing CO2 converter smelting → LF refining → CSP thin slab continuous casting → transverse tunnel heating furnace → TMCP six-stand four-roll continuous rolling → segmented laminar flow cooling → U-shaped coiling → inspection and warehousing. The chemical composition of the steel strip by weight percentage is as follows: C: 0.070wt%, Si: 0.30wt%, Mn: 1.40wt%, P: 0.015wt%, S: 0.010wt%, Als: 0.045wt%, V: 0.050wt%, Ti: 0.150wt%, Cr: 0.40wt%, Ca: 0.0050wt%, with the remainder being Fe and unavoidable trace elements.
[0068] In the converter smelting process, the S content of the molten iron is 0.035 wt%; carbon dioxide is blown into the bottom throughout the smelting process, with a bottom blowing gas supply intensity of 0.05 m³ / min. 3 / (t·min); The final dissolved [O] in molten steel is controlled at 850ppm. Steel sand is used for deoxidation and alloying with aluminum deoxidation, and SiMnFe, SiFe, and LCMnFe are used to prepare Si and Mn.
[0069] In the LF refining process, the molten steel undergoes aluminum deoxidation, V, Ti, and Cr microalloying, and calcium treatment in the LF furnace. The microalloying and calcium treatment processes are carried out with a wire feed rate of 3.5 m / s and a soft blowing time of 6 min after calcium treatment.
[0070] In the CSP thin slab continuous casting process, a two-strand vertical bending CSP thin slab continuous casting process is adopted. The casting process requires ladle protection casting and ladle slag detection and control. The continuous casting tundish temperature is 1565℃, the billet casting speed is 3.6m / min, carbon-free covering agent is used in the tundish, and low-carbon steel protective slag is used in the crystallizer to remove slag and protect carbon. The liquid level fluctuation in the crystallizer is controlled within ±3mm to ensure continuous casting.
[0071] In the transverse roller bottom tunnel heating furnace, the furnace exit temperature is controlled at 1200℃, the billet heating temperature is 1170℃, and the billet is kept at a constant temperature in the furnace to ensure that the microalloying elements are completely dissolved in the austenite region and to control the expansion of the austenite region.
[0072] In the continuous rolling process, the TMCP six-stand four-high continuous rolling process is adopted, with large reduction deformation. The reduction of F1, F2 and F3 mills is controlled to promote ferrite nucleation and refine grains. The reduction rates of F1, F2 and F3 mills are controlled at 55%, 45% and 35% or higher, respectively. High-pressure water descaling is ensured during the rolling process, with a descaling inlet pressure of 260 bar, an outlet pressure of 380 bar, a cooling rate of more than 20℃ / s, and a final rolling temperature of 940℃.
[0073] In the segmented laminar flow cooling, a multi-segment high-efficiency densified laminar flow cooling system consisting of a densified fine-tuning segment, a coarse-tuning segment, and another densified fine-tuning segment is adopted to achieve precise control of the internal structure of high-strength steel.
[0074] In the U-shaped winding process, the winding tension is 28 kN and the winding temperature is 630°C.
[0075] This invention also includes the following steps for continuous hot-dip galvanizing of high-strength steel with aluminum-magnesium coating: inlet uncoiling → laser welding → disc shearing → scale breaking machine → three-stage turbulent pickling → re-brushing and grinding → leveling machine → electromagnetic induction heating furnace → zinc pot → air knife → fan cooling → water quenching tank → finishing machine → tension leveling machine → roller coating machine → induction heating furnace → cooling air box → oiling → outlet coiling.
[0076] In the laser welding process, the welding speed is 38 mm / s, the welding machine power is 1500W, the laser diameter is 0.2 mm, and the defocusing amount is 295±0 mm. In the disc shearing edge: the shearing amount on one side is 10mm; In the three-stage turbulent pickling process: the acid bath temperature is 80℃ and the conductivity is 360ms / cm; In the re-brushing process: the re-brushing brush roller mode is 7 with an inlet brush roller mode of 1200 rpm and the outlet brush roller mode is 7 with a speed of 1200 rpm. The leveling mill has a rolling force of 4000 KN and an elongation of 0.3%. In the electromagnetic induction heating furnace: IH1 section 410℃, IH2 section 589℃, RTS section 670℃, HB section 419℃; hydrogen content 8%, process speed 50m / min; In the zinc pot: the zinc pot temperature is 450℃, the zinc liquid contains 22wt% Al, 6wt% Mg, 0.18wt% Si, 0.098wt% Ni, 0.03wt% Ce, 0.03wt% Ti, and the remainder consists of unavoidable impurity elements and Zn, with the total impurity element content not exceeding 1%. In the air knife: the air knife is 22mm away from the strip, the air knife pressure is 31mbar, the air knife height from the liquid surface is 125mm, the air knife lip gap is 1.4mm in the middle 450mm, and increases to both sides in 90mm increments of 0.02mm, with the outermost gap being 1.35mm. The edge baffle is 6.0mm thick and the distance between the edge baffle and the strip is 2mm. The main purpose is to reduce the thickening of the coating at the edge of the strip. During the cooling process of the fan: the cooling air volume of the fixed air box 0 is 20%, the air volume of the mobile cooling air box 1 is 75%, the air volume of the air box 2 is 82%, the air volume of the air box 1 in the upward section is 84%, the air volume of the air box 2 is 20%, the air volume of the air box 3 is 18%, the air volume of the air box 4 is 26%, the air volume of the air box 5 is 85%, and the temperature at the top of the tower is ≤256℃; In the aforementioned finishing mill: the rolling force is 2110KN, and the elongation is 0.02%; The tension leveling machine has a tension of 70T and an elongation of 0.15%. In the roller coating machine: the roller coating machine pressure is 3550KN, the roller speed ratio is 1 / 1.6, and the roller coating liquid is a chromium-free fingerprint-resistant passivation liquid; In the induction heating furnace: the heating temperature is 118℃; During the exit winding process: the winding tension is 180KN, and the winding speed is 55m / min.
[0077] The hot-rolled high-strength strip steel produced in this embodiment has the following properties: Mechanical properties: yield strength 620 MPa, tensile strength 750 MPa, elongation after fracture 22%; metallographic structure: F+P+carbides; grain size: grade 12. The high-strength zinc-aluminum-magnesium steel strip has the following properties: yield strength 700 MPa, tensile strength 780 MPa, elongation after fracture 20%; metallographic structure: F+P+carbides; grain size: grade 12; 180° bending test: no cracking of the substrate, no peeling of the coating; passivation solution film thickness controlled at 1.5 g / m² on both the upper and lower surfaces. 2 The adhesion amount of the zinc-aluminum-magnesium alloy coating on a single side and at a single point is controlled at 175g / m². 2 .
[0078] It should be understood that the specific embodiments described above are merely illustrative or explanatory of the principles of the invention and do not constitute a limitation thereof. Therefore, any modifications, equivalent substitutions, improvements, etc., made without departing from the spirit and scope of the invention should be included within the protection scope of the invention. Furthermore, the appended claims are intended to cover all variations and modifications falling within the scope and boundaries of the appended claims, or equivalent forms of such scope and boundaries.
Claims
1. A method for producing 750MPa grade high-strength zinc-aluminum-magnesium steel strip, characterized in that, Includes the following steps: Blast furnace smelting of molten iron → KR desulfurization pretreatment of molten iron → 120-ton top and bottom combined blowing CO2 converter smelting → LF refining → CSP thin slab continuous casting → transverse tunnel heating furnace → TMCP six-stand four-roll continuous rolling → segmented laminar flow cooling → U-shaped coiling → inspection and warehousing. The chemical composition of the steel strip, by weight percentage, is as follows: C: 0.060–0.070 wt%, Si: 0.10–0.30 wt%, Mn: 1.25–1.40 wt%, P: ≤0.015 wt%, S: ≤0.010 wt%, Als: 0.020–0.045 wt%, V: 0.040–0.050 wt%, Ti: 0.130–0.150 wt%, Cr: 0.25–0.40 wt%, Ca: 0.0020–0.0050 wt%, with the remainder being Fe and unavoidable trace elements.
2. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, In the converter smelting process: the S content of the molten iron is ≤0.035wt%; carbon dioxide is blown from the bottom throughout the smelting process, at a concentration of 0.02m³. 3 / (t·min)<bottom-blown gas supply intensity≤0.05m 3 / (t·min); The final dissolved [O] in molten steel is controlled at 600-850ppm, and steel sand is used for deoxidation and alloying with aluminum deoxidation, and SiMnFe, SiFe, and LCMnFe are used to prepare Si and Mn.
3. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, In the LF refining process: molten steel undergoes aluminum deoxidation, V, Ti, and Cr microalloying, and calcium treatment in the LF furnace. The microalloying and calcium treatment processes are carried out with a wire feeding speed of 3-3.5 m / s and a soft blowing time of 6 min after calcium treatment.
4. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, In the CSP thin slab continuous casting process: a two-strand vertical bending CSP thin slab continuous casting process is adopted. The casting process requires ladle protection casting and ladle slag detection and control. The tundish temperature is 1545~1565℃, the billet casting speed is ≥3.6m / min, carbon-free covering agent is used in the tundish, and low-carbon steel protective slag is used in the crystallizer to remove slag and protect carbon. The liquid level fluctuation in the crystallizer is controlled within ±3mm to ensure continuous casting.
5. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, In the transverse roller bottom tunnel heating furnace: the furnace outlet temperature is controlled at 1170-1200℃, the billet heating temperature is 1155-1170℃, and the billet is kept at a constant temperature in the furnace to ensure that the microalloying elements are completely dissolved in the austenite region and to control the expansion of the austenite region.
6. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, In the continuous rolling process: a TMCP six-stand four-high continuous rolling process is adopted, with large reduction deformation. The reduction of F1, F2, and F3 mills is controlled to promote ferrite nucleation and refine grains. The reduction rates of F1, F2, and F3 mills are controlled at 55%, 45%, and 35% or higher, respectively. High-pressure water descaling is ensured during the rolling process, with an inlet pressure of 200-260 bar, an outlet pressure of 300-380 bar, a cooling rate of more than 20℃ / s, and a final rolling temperature of 900-940℃.
7. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, In the segmented laminar flow cooling, a multi-segment high-efficiency densified laminar flow cooling system consisting of a densified fine-tuning segment, a coarse-tuning segment, and a densified fine-tuning segment is adopted to achieve precise control of the internal structure of high-strength steel.
8. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, In the U-shaped winding process: the winding tension is 15-28KN, and the winding temperature is 570-630℃.
9. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 1, characterized in that, The process also includes the following steps for continuous hot-dip galvanizing of high-strength steel with aluminum-magnesium coating: inlet uncoiling → laser welding → disc shearing → scale breaking machine → three-stage turbulent pickling → re-brushing and grinding → leveling machine → electromagnetic induction heating furnace → zinc pot → air knife → fan cooling → water quenching tank → finishing machine → tension leveling machine → roller coating machine → induction heating furnace → cooling air box → oiling → outlet coiling.
10. The method for producing a 750MPa grade high-strength zinc-aluminum-magnesium steel strip according to claim 9, characterized in that, In the laser welding process: welding speed 38mm / s, welding machine power 1500W, laser diameter 0.2mm, defocusing amount 295±0mm; In the disc shearing edge: the shearing amount on one side is 10mm; In the three-stage turbulent pickling process: the acid bath temperature is 80℃ and the conductivity is 360ms / cm; In the re-brushing process: the re-brushing brush roller mode is 7 with an inlet brush roller mode of 1200 rpm and the outlet brush roller mode is 7 with a speed of 1200 rpm. In the leveling mill: the rolling force is 3500-4000KN, and the elongation is 0.3%; In the electromagnetic induction heating furnace: IH1 section 410℃, IH2 section 589℃, RTS section 670℃, HB section 419℃; hydrogen content 8%, process speed 50m / min; In the zinc pot: the zinc pot temperature is 440-450℃, the zinc liquid contains 10-22 wt% Al, 2-6 wt% Mg, 0.2±0.02 wt% Si, 0.01±0.002 wt% Ni, 0.05±0.02 wt% Ce, 0.05±0.02 wt% Ti, and the remainder consists of unavoidable impurity elements and Zn, with the total impurity element content not exceeding 1%. In the air knife: the air knife is 22mm away from the strip, the air knife pressure is 31mbar, the air knife height from the liquid surface is 125mm, the air knife lip gap is 1.2-1.4mm in the middle 450mm, and increases to both sides in 90mm increments of 0.02mm, with the outermost gap being 1.35mm. The edge baffle is 6.0mm thick and the distance between the edge baffle and the strip is 2mm. The main purpose is to reduce the thickening of the coating at the edge of the strip. During the cooling process of the fan: the cooling air volume of the fixed air box 0 is 20%, the air volume of the mobile cooling air box 1 is 75%, the air volume of the air box 2 is 82%, the air volume of the air box 1 in the upward section is 84%, the air volume of the air box 2 is 20%, the air volume of the air box 3 is 18%, the air volume of the air box 4 is 26%, the air volume of the air box 5 is 85%, and the temperature at the top of the tower is ≤256℃; In the aforementioned finishing mill: the rolling force is 2110KN, and the elongation is 0.02%; The tension leveling machine has a tension of 70T and an elongation of 0.15%. In the roller coating machine: the roller coating machine pressure is 3550KN, the roller speed ratio is 1 / 1.6, and the roller coating liquid is a chromium-free fingerprint-resistant passivation liquid; In the induction heating furnace: the heating temperature is 118℃; During the exit winding process: the winding tension is 180KN, and the winding speed is 55m / min.